2007
DOI: 10.1016/j.jmb.2007.09.048
|View full text |Cite
|
Sign up to set email alerts
|

A 1.3-Å Structure of Zinc-bound N-terminal Domain of Calmodulin Elucidates Potential Early Ion-binding Step

Abstract: SummaryCalmodulin (CaM) is a 16.8 kDa calcium binding protein involved in calcium-signal transduction. It is the canonical member of the EF-hand family of proteins, which are characterized by a helixloop-helix calcium-binding motif. CaM is comprised of N-and C-terminal globular domains (NCaM and C-CaM), and within each domain there are two EF-hand motifs. Upon binding calcium, CaM undergoes a significant, global conformational change involving reorientation of the four helix bundles in each of its two domains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…A search for the crystallization conditions using the Hampton Research Crystal Screens I and II yielded tetragonal crystals (space-group P4 3 2 1 2), which contained also Zn 2+ ions in addition to Mg 2+ . Similar crystals of N-CaM obtained in the presence of Zn 2+ only have been previously reported by Warren et al (39). Upon further search we have obtained triclinic crystals of N-CaM in the presence of Mg 2+ only.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A search for the crystallization conditions using the Hampton Research Crystal Screens I and II yielded tetragonal crystals (space-group P4 3 2 1 2), which contained also Zn 2+ ions in addition to Mg 2+ . Similar crystals of N-CaM obtained in the presence of Zn 2+ only have been previously reported by Warren et al (39). Upon further search we have obtained triclinic crystals of N-CaM in the presence of Mg 2+ only.…”
Section: Resultssupporting
confidence: 88%
“…The structure was solved by molecular replacement using the coordinates of N-CaM structure obtained in the presence of Zn 2+ only (39)(PDB code 2PQ3). Both Ca 2+ -binding loops of N-CaM in the Mg/Zn-N-CaM crystal contain an octahedrally coordinated metal ion.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, the T state represents a collection of structures that may differ somewhat in the conformation of the calcium-binding sites, but whose overall structure resembles that of apo calmodulin. The existence of an ion-bound form that resembles the apo conformation has recently been established (51). Likewise, the R state is a collection of structures that resemble the reported open structure of active calmodulin (52,53).…”
Section: Discussionmentioning
confidence: 93%
“…Here, examination of elements, such as Ca, Mg, Fe, Zn, and Cu, previously shown to promote or suppress X. fastidiosa biofilm formation (29) indicated that only Ca increased twitching motility in vitro. Ca binding was confirmed for the recombinant PilY1-1611 protein, and while Mg was also detected in the purified protein, the failure of this element to modulate twitching suggests that this could be due to the fact that Ca-binding motifs can also bind other divalent cations (49,50). Chelation of extracellular Ca by EGTA produced larger (on agar plates) and faster (in microfluidic chambers) decreases in twitching than intracellular chelation (BAPTA/AM), a finding consistent with the easy removal of Ca from exposed proteins or other molecules.…”
Section: Discussionmentioning
confidence: 87%